NURSING DIAGNOSES AND RISK OF HEMATOMA AND BLEEDING FOR VASCULAR PROCEDURES PERFORMED IN A LARGE HOSPITAL IN NORTHERN MINAS GERAIS - Oliveira Farias, Janaína; Silva Moraes, Daniel; Lopes de Figueiredo, Mirela; Scremin, Marlete; Tamires Souza Vieira, Júnia; Esméria Neta, Maria; Fagundes Souto, Daniella; Beatriz Lima Pimenta, Márcia; Gonçalves Grillo, Marcell; Gonçalves Silva, Dinariam; Lilian Pereira de Oliveira, Émile; Lucciane Alves Maria, Emmilly; et al. (Health and Society, 2026)
The World Health Organization (WHO) estimates that in the year 2030, approximately 23.6 million people will die as a result of cardiovascular diseases. Thus, nursing care becomes essential for comprehensive care, as well as for the recovery of clients with cardiovascular and cerebrovascular diseases through the systematization of nursing care. This study aimed to identify the main nursing diagnoses of patients undergoing endovascular therapy in a large hospital located in the north of Minas Gerais and to associate conditions sensitive to the risk of hematoma and bleeding. It refers to a descriptive, documentary study with a quantitative approach that was carried out in the endovascular therapy sector of Santa Casa de Montes Claros - MG. Data analysis was performed using descriptive statistics and bivariate analysis. The study universe consists of 1,266 medical records of clients, who were treated at the endovascular diagnosis and therapy service and underwent therapeutic procedures in the period from 2017 to 2019. 59.0% were female, mean age 65.3 (± 13.6), the main comorbidity was arterial hypertension (68.4%) and the most common procedure was coronary angioplasty (67.6%). The most prevalent diagnosis was the risk of hematoma and bleeding (44.4%), which was associated with sex, medications, arterial hypertension, health insurance and other diagnoses. Thus, it is important that nurses know how to classify and identify risks and complications in relation to endovascular procedures so that a care plan is applied according to the patient’s need.